Bowel cancer screening in England: a qualitative study of GPs' attitudes and information needs. - Woodrow, C; Rozmovits, L; Hewitson, P; Rose, P; Austoker, J; Watson, E (2006)
BACKGROUND: The National Health Service Bowel Cancer Screening Programme is to be introduced in England during 2006. General Practitioners are a potentially important point of contact for participants throughout the screening process. The aims of the study were to examine GPs' attitudes and information needs with regard to bowel cancer screening, with a view to developing an information pack for primary care teams that will be circulated prior to the introduction of the programme. METHODS: 32 GPs participated in semi-structured telephone interviews. 18 of these had participated in the English Bowel Screening Pilot, and 14 had not. Interviews covered attitudes towards the introduction of the Bowel Cancer Screening Programme, expected or actual increases in workload, confidence in promoting informed choice, and preferences for receiving information about the programme. RESULTS: GPs in the study were generally positive about the introduction of the Bowel Cancer Screening Programme. A number of concerns were identified by GPs who had not taken part in the pilot programme, particularly relating to patient welfare, patient participation, and increased workload. GPs who had taken part in the pilot reported holding similar concerns prior to their involvement. However, in many cases these concerns were not confirmed through GPs experiences with the pilot. A number of specific information needs were identified by GPs to enable them to provide a supportive role to participants in the programme. CONCLUSION: The study has found considerable GP support for the introduction of the new Bowel Cancer Screening Programme. Nonetheless, GPs hold some significant reservations regarding the programme. It is important that the information needs of GPs and other members of the primary care team are addressed prior to the roll-out of the programme so they are equipped to promote informed choice and provide support to patients who consult them with queries regarding screening.